Analysis of Road Maintenance Between Burda Fast And Hotmix: A Case Study in Road Section Bojonegoro (Pajeng) –Nganjuk (Guyangan) - Samsul Widjajanto; Hera Widyastuti (Journal of Civil Engineering, 2025)
The East Java Provincial Government through the Public Works Department of Highways has a road improvement and maintenance work program to maintain road stability. However, in its implementation, it is often faced with less-than-ideal conditions, such as natural disasters, resulting in a reduced budget for the work program. Therefore, an alternative method for maintaining asphalt pavement is needed which has advantages in terms of cost efficiency, but does not reduce quality and also does not require a more complicated process compared to carrying out road maintenance work which was usually carried out in previous years, (by using Hotmix). In this research, fast burda was used as an alternative to Hotmix for asphalt road maintenance, namely making fast burda from 2 x 3 cm coarse aggregate, 1 x 2 cm aggregate, 1 x 1 cm aggregate, and 60/70 penetration asphalt. The method used in the research is to compare road maintenance work using fast burda and Hotmix. The analysis carried out in this research is a comparison of the duration of work time, service life and cost analysis between work using fast burda and using Hotmix. The results of this research show that the duration of work with a 1 m2 sample for asphalt road patching using hot mix is the same as road patching using fast burda. The service life of road patches using Hotmix is longer than road patching using fast burda, namely fast burda starts to experience damage in the 5th month, while Hotmix starts to experience damage in the 6th month. Meanwhile, in terms of costs, work using fast burda is cheaper compared to work using Hotmix, fast burda requires IDR303.355 per square meter, while Hotmix requires IDR318.84 per square meter. So the difference in implementation costs per square meter is IDR15.490. Burda can quickly be used as an alternative method for maintaining asphalt pavement when budget conditions are reduced due to national problems or natural disasters.